Hubungan dan Pengaruh Audit Internal atas Fungsi Produksi untuk Menilai Efektivitas dan Efisiensi Proses Produksi - Thomas, Gen Norman (Bina Nusantara University, 2012)
The objective of this study is to examine the relationship and the influence between the internal audit toward production function to assess effectiveness and efficiency of the production process at PT.Sumber Nitrat Jaya. The type of research is survey with descriptive research and analysis technique used is the analysis of qualitative data and quantitative data analysis. The sample was 30 respondents. Based on the significance test of correlation coefficients between the variables, it shows a correlation between internal audit with the production function to assess the effectiveness and efficiency of the production process obtained a correlation coefficient of 0.950, which means there is a very strong relationship. By testing the hypothesis that the correlation of the results obtained there is a significant relationship between internal audit with the production function to assess the effectiveness and efficiency of production processes in PT Sumber Nitrat Jaya, because of Ho1 was rejected and Ha1 was accepted where t count HA1> T Table (16.156>2.048). Significance test based on the regression parameter showed a simple linear regression of Y = 4.523 + 0.581 X + Îµ. This is supported by testing hypotheses derived regression t count> T Table (16.156> 2.048) then there is a significant influence of internal audit toward the production function to assess the effectiveness and efficiency of production processes in PT Sumber Nitrat Jaya because Ho2 was rejected and Ha2 was accepted. This is also supported by the R square value of 0.903 obtained results, or 90.3%. This shows the contribution of internal audit in explaining the effectiveness and efficiency of production processes by 90.3% while the remaining 9.7% is explained by other factors not examined or not included in the model.